TCR+/BCR+ dual-expressing cells and their associated public BCR clonotype are not enriched in type 1 diabetes - Japp, Alberto Sada; Meng, Wenzhao; Rosenfeld, Aaron M.; Perry, Daniel J.; Thirawatananond, Puchong; Bacher, Rhonda L.; Liu, Chengyang; Gardner, Jay S.; Atkinson, Mark A.; Kaestner, Klaus H.; Brusko, Todd M.; Naji, Ali; et al. (Cell, 2021)
Ahmed and colleagues recently described a novel hybrid lymphocyte expressing both a B and T cell receptor, termed double expresser (DE) cells. DE cells in blood of type 1 diabetes (T1D) subjects were present at increased numbers and enriched for a public B cell clonotype. Here, we attempted to reproduce these findings. While we could identify DE cells by flow cytometry, we found no association between DE cell frequency and T1D status. We were unable to identify the reported public B cell clone, or any similar clone, in bulk B cells or sorted DE cells from T1D subjects or controls. We also did not observe increased usage of the public clone VH or DH genes in B cells or in sorted DE cells. Taken together, our findings suggest that DE cells and their alleged public clonotype are not enriched in T1D. This Matters Arising paper is in response to Ahmed et al. (2019), published in Cell. See also the response by Ahmed et al. (2021), published in this issue. [Display omitted] •DE cells not increased in blood or lymphoid tissue of T1D subjects compared to controls•Failure to replicate results of Ahmed et al. with identical FACS assay•“Public” clone-x BCR sequence not found in blood or spleen of T1D and controls•CDR3 AA sequences similar to clone-x are not enriched in B cells or sorted DE cells There does not appear to be increased abundance of dual-expresser TCR+/BCR+ lymphocytes in type I diabetes patients, nor a public clonotype, challenging the results of a previous study.